The “Normalization” of Intersex Bodies and “Othering” of Intersex Identities in Australia - Carpenter, Morgan (Journal of bioethical inquiry, 2018)
Once described as hermaphrodites and later as intersex people, individuals born with intersex variations are routinely subject to so-called “normalizing” medical interventions, often in childhood. Opposition to such practices has been met by attempts to discredit critics and reasserted clinical authority over the bodies of women and men with “disorders of sex development.” However, claims of clinical consensus have been selectively constructed and applied and lack evidence. Limited transparency and lack of access to justice have helped to perpetuate forced interventions. At the same time, associated with the diffusion of distinct concepts of sex and gender, intersex has been constructed as a third legal sex classification, accompanied by pious hopes and unwarranted expectations of consequences. The existence of intersex has also been instrumentalized for the benefit of other, intersecting, populations. The creation of gender categories associated with intersex bodies has created profound risks: a paradoxically narrowed and normative gender binary, maintenance of medical authority over the bodies of “disordered” females and males, and claims that transgressions of social roles ascribed to a third gender are deceptive. Claims that medicalization saves intersex people from “othering,” or that legal othering saves intersex people from medicalization, are contradictory and empty rhetoric. In practice, intersex bodies remain “normalized” or eliminated by medicine, while society and the law “others” intersex identities. That is, medicine constructs intersex bodies as either female or male, while law and society construct intersex identities as neither female nor male. Australian attempts at reforms to recognize the rights of intersex people have either failed to adequately comprehend the population affected or lacked implementation. An emerging human rights consensus demands an end to social prejudice, stigma, and forced medical interventions, focusing on the right to bodily integrity and principles of self-determination.